Gadskārtu svētki kultūras izpratnes sekmēšanas līdzeklis pirmsskolā - Meļķe, Mārīte (Latvijas Universitāte, 2022)
Diplomdarba temats: Gadskārtu svētki kultūras izpratnes sekmēšanas līdzeklis pirmsskolā. Mērķis: teorētiski un empīriski pētīt gadskārtu svētku iepazīšanas iespējas pirmsskolas pedagoģiskajā procesā bērna kultūras izpratnes sekmēšanai. Diplomdarba autore pētīja, kā bērni pirmsskolas vecumā ģimenēs un pirmsskolas izglītības iestādē iepazīst latviešu gadskārtu svētku tradīcijas un vai to iepazīšana un apgūšana sekmē kultūras izpratnes veidošanos bērniem pirmsskolā, analizēja gadskārtu svētku lomu kultūras izpratnes veidošanā bērniem pirmsskolas pedagoģiskajā procesā. Pirmajā nodaļā tika teorētiski apskatīts Kultūras izpratnes jēdziens, raksturots Kultūras izpratnes sasniedzamais rezultāts tradīciju apguvē pirmsskolā, kā arī analizēts gadskārtu svētku saturs un metodika kultūrizpratnes veicināšanai pirmsskolā. Tika analizēta jaunā mācību programma, tās mērķi un uzdevumi, analizētas, raksturotas mācību metodes. Otrajā nodaļā tika pētīts, kā sekmēt bērna kultūras izpratni gadskārtu svētku tradīciju iepazīšanas procesā pirmsskolā. Tika atlasītas pētījuma metodes, izstrādāti kultūrizpratnes kritēriji, rādītāji un līmeņi. Tika veikts sākotnējais un atkārtotais bērnu kultūrizpratnes vērojums, veikta izmēģinājumdarbība, pētījumā iegūto rezultātu analīze un salīdzināšana. Tika novērotas pirmsskolas skolotāju pedagoģiskās darbības rotaļnodarbībās pirmsskolā no 1.septembra līdz 1.novembrim, veļu laikā un rudens gadskārtu svētkos Rudenājos ar 5 - 6 gadus veciem bērniem. Tika veikta pirmsskolas izglītības iestādes skolotāju anketēšana. Veicot pētījumu, darba autore secināja, ka gadskārtu svētki sekmē bērna kultūrizpratnes veidošanos. Un, ka pirmsskolas izglītības skolotāja praktiskā pieredze, spēja būt ieinteresētam, rada vidi, kurā bērns spēj gūt vairāk zināšanu, prasmju un attieksmju, iepazīstot tradicionālo kultūru un gadskārtu svētku tradīcijas. Diplomdarba apjoms: 79 lpp, 2 nodaļas, 9 apakšnodaļas, 4 tabulas, 7 attēli, 42 literatūras avoti, 5 pielikumi. Pētījuma teorētiskā daļa balstās uz gadskārtu svētku tradīciju satura un metodikas raksturojumu un nozīmīgumu kultūrizpratnes sekmēšanai pirmsskolā.

Topic of Qualification Thesis: “Seasonal Folk Celebration as a Means of Promoting Cultural Literacy in Preschool”. Aim: To study theoretically and empirically the possibilities of getting acquainted with seasonal folk celebration within the framework of preschool teaching process for the purpose of promoting cultural literacy of a child. The author of the Qualification Thesis studied how children of pre-school age get acquainted with seasonal folk celebration within their families and preschool education institutions and whether this learning process contributes to promoting cultural literacy in preschool, analysed the role of seasonal folk celebrations in raising cultural literacy for children at the preschool teaching process. The first section covers theoretical overview of the term “cultural literacy“, description of cultural literacy related objectives in the process of tradition awareness at pre- schooling as well as analysis of the content of seasonal folk celebrations and the methodology for promoting cultural literacy in preschool. The new teaching programme, its objectives and tasks as well as teaching methods were analysed and described. The second section covers examination of means of promoting cultural literacy of a child within the process of getting acquainted with seasonal folk celebration traditions at the preschool level. Research methods were selected and criteria, indicators and levels of cultural literacy were developed. The initial and repeated cultural literacy observation was carried out, the testing activity was performed as well as analysis and comparison of the results accumulated during the research phase were made. The teaching activities of preschool teachers were observed during playing lessons within the period from September 1 to November 1, during All Souls Day and autumn season called “Rudenāji” celebrations within the group of children 5 to 6 years of age. The teachers of the pre-school educational establishment were asked to fill in questionnaires. The research carried out has led the author of the Qualification Thesis to the conclusion that seasonal folk celebration promotes cultural literacy in preschool. The practical experience of a preschool teacher and her/his ability to be interested in the subject are preconditions for developing an environment in which a child is able to accumulate more knowledge, skills and attitudes through the awareness of traditions of seasonal folk celebration. Volume of Qualification Thesis: 79 pages, 2 sections, 9 subsections, 4 tables, 7 pictures, 42 literature sources, 5 appendices. The theoretical part of the study is based on the characterization of the content and methodology as well as on importance of seasonal folk celebration in promoting cultural literacy in preschool. Keywords: preschool teaching, cultural literacy, seasonal folk celebration
Seasonal Folk celebration as a means of promoting cultural literacy in preschool
Keywords: Pedagoģija; pedagoģiskais process pirmsskolā; kultūrizpratne; gadskārtu svētki; Rudenāji